PENGGUNAAN TEKNOLOGI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK MENGHITUNG PERSENTASE RUANG TERBUKA HIJAU DI DAERAH PERMUKIMAN KOTA DENPASAR - Nuarsa, I Wayan (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstrak Green open space (GOS) is a very important component in the arrangement of urban space, because the GOS has the function of ecological, aesthetic, social, cultural, and economic. Calculating of the GOS can easily be done in area that are enable for such purposes as urban forests, recreational areas of the city, as well as agricultural areas. However, for the land use consisting of non-GOS and GOS such as settlement, calculation of the GOS will be quite difficult. This research was conducted to measure the percentage of the GOS in settlement areas in the Denpasar city using remote sensing and geographic information system technology. The results of this study showed that the percentage of the GOS in the settlements area of Denpasar ranged from 2.97% to 30.01%, with an average value of 14, 43%, and a standard deviation of 7.32% or 182.98 m2. The majority (50%) of the percentage of the GOS in the settlements area in the Denpasar city classified as moderate (10– 20%), 32% are low (<10%), and only 18% had a high percentage of the GOS (> 20%). Factors that influence to the percentage of the GOS in the settlement area of Denpasar is the location of the sattements and the land area per housing unit.
Keywords: Keywords: green open space, remote sensing, gis, ikonos, settlements